Atroposelective Synthesis of Axially Chiral All‐Benzenoid Biaryls by the Gold‐Catalyzed Intramolecular Hydroarylation of Alkynones. Issue 26 (23rd August 2016) - Satoh, Masakazu; Shibata, Yu; Kimura, Yuki; Tanaka, Ken
Abstract : The cationic gold(I)/( R )‐xyl‐binap complex was shown to catalyze the atroposelective intramolecular hydroarylation of alkynones to produce enantioenriched axially chiral all‐benzenoid biaryls, 4‐aryl‐2‐naphthol derivatives, with up to 67 %  ee . The reaction of a racemic alkynone in the presence of the same gold(I) catalyst also afforded the corresponding axially chiral all‐benzenoid biaryl in excellent yield with 70 %  ee . Abstract : The cationic gold(I)/( R )‐xyl‐binap complex catalyzes the atroposelective intramolecular hydroarylation of alkynones to produce enantioenriched axially chiral all‐benzenoid biaryls, 4‐aryl‐2‐naphthol derivatives, with up to 67 %  ee . The reaction of a racemic alkynone in the presence of the same gold(I) catalyst also affords the corresponding axially chiral all‐benzenoid biaryl in excellent yield with 70 %  ee .